Near Shore FLNG Concept Evaluations - Corneliussen, Martin; Samnøy, Eirik (NTNU, 2015)
This study evaluates different solutions for a LNG facility, partially placed on shore and partially placed on a floater, hereby referred to as at-shore FLNG. There are several advantages with this solution where reduced cost, shorter development time and potential for standardization is highlighted as the greatest. To illustrate the challenges for an at-shore FLNG project, two main scenarios linked to a potential location for LNG production have been identified. The chosen locations are the Gulf of Mexico and Northern Norway. An initial configuration for liquefaction, refrigerant compressor driver, NGL extraction, heat generation and cooling has been established based on weather data, governmental restrictions and local conditions at the locations. The result of this configuration has been calculated using HYSYS and reference data. Next, the process or utility systems have been swapped with other configuration alternatives. This is done one alternative at the time, and the result has been measured against the initial result to identify and quantify the consequence of other process or utility systems. The desired production rate is approximately 4 MTPA, but this varies at the different configuration alternatives. Additionally, all configurations are simulated with average and high temperature to identify and quantify the consequences this have for the plant efficiency and capacity. Next, three subcases, each linked to other potential locations for LNG production, has been identified to evaluate the consequences of combining more than one alternative at the time. The alternative system combination is considered the most likely combination at the given location. The potential locations for the subcases are the west coast of Canada, the Northwest coast of Russia and the Northwest coast of Australia. As for the scenarios, the subcases are simulated with average and high temperature. Complete process models of the different scenarios and subcases have been made in HYSYS and the simulation results forms the main basis ...